Motor and sensory responses after percutaneous tibial nerve stimulation in multiple sclerosis patients with lower urinary tract symptoms treated in daily practice. (3rd January 2014) - Zecca, C.; Digesu, G. A.; Robshaw, P.; Puccini, F.; Khullar, V.; Tubaro, A.; Gobbi, C.
<x xml:space="preserve">Abstract</x> Background and purpose Posterior tibial nerve stimulation (PTNS) is an effective treatment option for lower urinary tract symptoms (LUTS) in multiple sclerosis (MS) patients. Methods Patients with MS and LUTS unresponsive to medical treatment received PTNS for 12 weeks after saline urodynamics to evaluate the prevalence of motor, sensory and combined responses during PTNS and to determine whether the type of response can predict treatment outcome. LUTS were also assessed using a 3‐day bladder diary, patient perception of bladder condition (PPBC) questionnaire, patient perception of intensity of urgency scale (PPIUS), Kings Health QOL questionnaire (KHQ) and Overactive Bladder Questionnaire (OAB‐q) before and after treatment. Patients were considered as "responders" if they reported an improvement >50% in their LUTS according to the PPBC. Sensory, motor and combined sensory/motor responses were compared between responders and non‐responders. Results Eighty‐three patients were included. 61% (51/83) of patients were responders. Sensory, motor and combined sensory/motor responses were found in 64% (53/83), 6% (5/83) and 30% (25/83) of patients respectively. A sensory response alone, or in combination with a motor response, was better associated with a successful outcome than the presence of a motor response alone (P = 0.001). Conclusions A sensory response, either alone or in combination with a motor response, is more frequent and seems to be better associated with a successful outcome of PTNS than motor response alone.